To apply the zero power rule, we need to remember that any nonzero number raised to the power of zero is equal to 1. Therefore, we can simplify the expression as follows:
- \((-33)^0 = 1\)
- \(27^0 = 1\)
Now we can substitute these values into the expression:
\[ 9 • (-33)^0 + \frac{3}{2} (8 - 27^0) = 9 • 1 + \frac{3}{2} (8 - 1) \]
Now we can fill in the blanks in the expression:
\[ 9 • (-33)^0 + \frac{3}{2} (8 - 27^0) = 9 • 1 + \frac{3}{2} (8 - 1) \]
So, the equivalent expression is:
\[ 9 • 1 + \frac{3}{2} (8 - 1) \]